Development and application of an ethical consumption behavior scale: Evidence from retail consumers in the Mekong delta, Vietnam - Truong, Le Minh; Trai, Nguyen Van; Ha, Nguyen Hong (Edelweiss Applied Science and Technology, 2026)
This study aims to develop and validate a scale for measuring ethical consumer behavior tailored to the socio-cultural context of retail consumers in the Mekong Delta, addressing limitations of existing international scales when applied in Vietnam. Based on the Theory of Planned Behavior (TPB), the model examines relationships among attitude, subjective norms, perceived behavioral control, intention, and ethical consumer behavior. Data were collected and analyzed in multiple stages with independent samples, utilizing Cronbach's Alpha, EFA, CFA, and SEM techniques. Results demonstrate that the scales exhibit good reliability and validity, with a new factor emerging that reflects consumers' ethical and sustainable orientation. Structural model analysis shows that subjective norms and perceived behavioral control positively influence both intention and ethical behavior, whereas attitude does not significantly impact intention. Notably, the relationship between intention and behavior was not confirmed, indicating a gap between perception and action in ethical consumption. The study contributes theoretically by refining a localized scale and suggests future research directions to better understand how intention translates into behavior within emerging economies.